IMPLEMENTASI BAHASA MADURA SEBAGAI MUATAN LOKAL DALAM KURIKULUM 2013 SMK NEGERI I PAMEKASAN - Mahordi (LPPM STKIP PGRI Sidoarjo, 2022)
As a regional language used by the Madurese community, normatively the Madurese language has served as a means of communication between community groups that are geographically located in four districts, namely Bangkalan, Sampang, Pamekasan, Sumenep, and the surrounding areas. With the use of Indonesian as the only language of instruction from an early age at SekolahD, the Madurese language has been marginalized, because it is only used as a subject to fill local content. Students are no longer required to master the Madurese language properly and correctly. This condition is exacerbated by the fact that many young Madurese couples are reluctant to use the Madurese language as a language of communication in their daily lives. The above facts are acknowledged or not, sooner or later will drag the Madurese language in a position squeezed by the circumstances of the times. This research is a descriptive research with a qualitative approach. This study focuses on the implementation of the Madurese language as local content in the 2013 curriculum of SMK Negeri I Pamekasan. The results showed that the implementation of the Madurese language as a local content in SMK Negeri I Pamekasan was based on the Pamekasan Regency Regional Regulation No. 13 of 2006 concerning the system of providing education in Pamekasan district which requires the teaching of Madurese language to be given from kindergarten to high school / vocational level. With the stipulation of the 2013 curriculum as the Madura language national curriculum, it has a special place as local content lessons, this refers to the East Java Governor's Regulation (PERGUB) Number 19 of 2014 concerning regional language subjects as Mandatory Local Content in schools/Madrasah in East Java. The regulation is intended as a vehicle to instill aesthetic, ethical, moral, spiritual, and character educational values. Meanwhile, the aim is to preserve, develop, and create regional languages ​​and literature, which are regional assets and wealth. Regarding the implementation of the Madurese language as local content at SMK Negeri 1 Pamekasan, the results are less than optimal, this occurs because the Madurese language teacher is not a teacher who has linguistic competence, this can be seen from the implementation of Madurese language learning which includes Planning, Implementation, and Evaluation.